How not to stimulate local development. Syndromes of failures in the absorption of exogenous factors in local development governance based on the example of Polish small towns - Sztando, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The absorption of exogenous factors represents one of the main components of local development governance (LDG). Today, in many countries, it is facilitated by numerous supra-local determinants. It primarily refers to these countries where local governments take advantage of the financial support of the EU. This absorption, however, experiences occasional failures which have various reasons and effects. The article presents the results of research in this subject matter conducted in Poland. They were carried out in two phases. The first covered participant observations performed in the period 2000-2014 in 61 Polish municipalities, aimed at the identification of the a.n. failures characteristics and their typical patterns. The second focused on determining the prevalence and reasons for these patterns occurrence in local development governance of Polish small towns. Long personal interviews, conducted in 2014 with the mayors of 46 such towns, were used in its course. The article is concluded with recommendations related to the improvement of local and supra-local governance of local development and focused on the reduction of the number and consequences of absorption failures
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 49-69
Keywords: municipality; local development governance; local development; local authorities; small town; exogenous factors of local development; Poland; gmina; władze lokalne; rozwój lokalny; zarządzanie rozwojem lokalnym; małe miasto; egzogeniczne czynniki rozwoju lokalnego; Polska